Alternative Strategies for Controlling Reproductive Infectious Diseases of Beef Cattle to Increase Reproduction Eficiency - Adjid, R M Abdul (Indonesian Animal Sciences Society, 2004)
Reproductive infectious diseases affect reproductive organs cause inefficiency in reproduction of cattle. In Indonesia, there are six infectious diseases of reproduction in beef cattle, namely Brucellosis, Leptospirosis, Infectious Bovine Rhinotracheitis (IBR), Bovine Viral Diarrhea (BVD), Bluetongue and Toxoplasmosis. Although report of the occurrence of the diseases is limited for only certain areas of Indonesia, because of limitation of veterinary laboratories available in this country, those diseases have potential to distribute wider and cause more economic impact if the diseases were not prevented and controlled properly by the government and farmers together . Approaches should be taken for diseases control and prevention are in-flock and inter-flock of beef cattle. Alternative strategies suggested for diseases control are: (1). Flock free of the disease; (2). Biosecurity; and (3). Artificial Insemination using semen free of the diseases. Research and development of reproductive infectious diseases on beef cattle should be improved to support and contribute the development of beef cattle agribusiness program in this country. Key words: Beef cattle, mproductive infectious diseases, alternative control strategy